2018
DOI: 10.3390/ijerph15091934
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Related Health Care Needs in Refugees—A Current Three Center Experience in Europe

Abstract: Background: Immigration into Europe has reached an all-time high. Provision of coordinated healthcare, especially to refugee women that are at increased risk for adverse pregnancy outcomes, is a challenge for receiving health care systems. Methods: We assessed pregnancy rates and associated primary healthcare needs in three refugee cohorts in Northern Germany during the current crisis. Results: Out of n = 2911 refugees, 18.0% were women of reproductive age, and 9.1% of these were pregnant. Pregnancy was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
1
29
1
1
Order By: Relevance
“…For example, a different study, also located in northern Germany, reported only 9% of the refugee women in this age group. 32 The higher rates in our study might be explained by the fact that our ratio is based on women using healthcare and not on the general female refugee population of reproductive age. Other studies based on the general refugee population and/or including screening measures reported comparable differences to our study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, a different study, also located in northern Germany, reported only 9% of the refugee women in this age group. 32 The higher rates in our study might be explained by the fact that our ratio is based on women using healthcare and not on the general female refugee population of reproductive age. Other studies based on the general refugee population and/or including screening measures reported comparable differences to our study.…”
Section: Discussionmentioning
confidence: 64%
“…Pregnant refugees are a vulnerable patient group with increased healthcare utilisation. 32 Despite the fact that they were allowed to use gynaecologists, midwives and nursing care, 14 it was de facto hardly possible to get this kind of support during the specific situation of 2015–2016. In order to prevent adverse health outcomes, 41 care for pregnant women was included in the primary care for refugees in our walk-in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of full time primary medical care at an onsite ward of the asylum seeker residence—with patient specific documentation of visit time and frequency—was unique to the here presented cohort and ideal for the conducted analysis. In other cohorts thus far analyzed by our team, similar analysis is hampered by limited data extraction of residence time and medical records that could only be obtained by a proportion of asylum seekers or were collected in a different fashion than in the here described cohort [ 15 , 16 , 17 , 19 , 20 , 23 , 24 ]. Currently, however, we aim at harmonizing and analyzing further large asylum seeker cohorts of a similar kind to see whether our results can be confirmed in a greater specimen of migrants entering Western Europe during the current crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Data on primary medical care provision from two migrant reception centers in Celle and Friedland, Germany were included into this analysis. The study cohorts consisted of n = 3104 refugees housed in Celle between September 2015 and June 2016 (parts of this cohort have been previously described [ 8 ]) and n = 7327 refugees housed in Friedland between August 2017 and January 2019 (parts of this cohort were previously described [ 9 ]). Refugees were accommodated in these reception facilities for a transitional period of a few weeks up to several months.…”
Section: Methodsmentioning
confidence: 99%